Pemmali Culture in Bugis Community versus Law Enforcement of Age of Marriage in the Religious Courts - Aris Aris; Rosdalina Bukido (Jurnal Ilmiah Al-Syir'ah, 2022)
This study aims to explore the law enforcement of age of marriage in Bugis community, Islamic law and national law, and pemmali culture as one of the most crucial reasons for marriage dispensation. This study method used a sociological juridical research with normative and formal juridical approaches, socio-anthropological and case studies. Data analysis techniques used positivist theory of legal system, law enforcement, and sociology of legal system. The results showed that the enforcement of age of marriage in Bugis community does not have an age standard determination unless the daughter is menstruating, the application of pemmali culture causes daughter to become victims of underage marriages, they are blind to knowledge of age of marriage in Law Number 16 of 2019. The application of marriage age for children are still debated by the majority of fiqh scholars as long as girls have not menstruated, they do not question child marriage if it is menstruating, but Indonesian national law there is no way to legalize child marriage before getting a marriage dispensation. Pemmali culture can be determined as one of the reasons for the sharp increase in marriage dispensations in Religious Courts due to the mindset of parents in Bugis community when their daughters are underage and are proposed three times by men. A mayor implication of these findings is to reduce the amount of marriage dispensation recommended the next research on the effectiveness of socialization of Law Number 16 of 2019.